THE ANALYSIS OF WOMAN’S CREDIBILITY AS A LEADER CASE STUDY AT THE REPRESENTATIVE OFFICE OF OMBUDSMAN IN NORTH SULAWESI - Melinda, Warokka .; Saerang, David P.E (FEB Universitas Sam Ratulangi Manado, 2018)
Abstract: Leaders become important figures in the institution. A leader is not relying on the title that he or she has, who he or she is, from where he or she comes from, even the gender man or woman. Yet, some facts argue that women are still under-represented in terms of leadership. To be an effective leader, she or he needs to be credible. There are three aspects of credibility which are trustworthiness, expertise, and inspiration. The research aims to analyse woman’s credibility as a leader in Representative Office of Ombudsman in North Sulawesi. This study uses descriptive qualitative research. The data gathered in this research are primary data and secondary data such as interviews and documentations. The validity and reliability of data in this research are tests through triangulation test and there are 14 informants as the sample which is the entire employee in Representative Office of Ombudsman in North Sulawesi. The result of this research shows that all the informants perceive that woman leader in this institution is credible and reflects from her leadership all the informants are agree that women leaders could be credible leader. To be a good leader, woman has to build credibility. Keywords: woman leader, credibility